2011
DOI: 10.1002/dac.1204
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation methods for integrated services

Abstract: SUMMARYReservation aggregation provides scalability to the IETF Integrated Services (IntServ) by reducing the high number of states stored at internal routers and the number of signaling messages processed at these routers. However, in the case of frequent joining and leaving of individual flows, the latter benefit will be lost due to frequent adjustment of aggregation size. In this paper, to reduce aggregation adjustment frequency, we focus on investigating two critical parameters: aggregation size and the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…In our scheme, the trustworthiness of a node is considered as the credibility factor of its recommendation, as shown in (5). The number of common friends is denoted by C(u,v,t).…”
Section: Recommendation Metricmentioning
confidence: 99%
See 2 more Smart Citations
“…In our scheme, the trustworthiness of a node is considered as the credibility factor of its recommendation, as shown in (5). The number of common friends is denoted by C(u,v,t).…”
Section: Recommendation Metricmentioning
confidence: 99%
“…The number of common friends is denoted by C(u,v,t). In our scheme, the trustworthiness of a node is considered as the credibility factor of its recommendation, as shown in (5). Opinions from trustworthy nodes are considered more credible and weighted more than those from untrustworthy nodes, thus reducing the risk of malicious attacks.…”
Section: Recommendation Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, integrated methods were increasingly used in . Lin and Labiod proposed a method to integrate the parameter‐based policy and measure‐based policy. The results showed that the mechanisms they proposed outperformed other policies which only considered the parameter.…”
Section: Related Workmentioning
confidence: 99%
“…The methods for elimination of impulsive noise [10,11] as well as problems related with vectoring process used in VDMT [12] and high number of its sub-channels [13,14] are being discussed as well [15]. Another potential method for increasing the resulting transmission rate in G.fast is to use channel bonding and to aggregate several separate channels together [16,17]. Moreover, this idea was further extended by the application of phantom virtual circuits in star-quad metallic cables [18].…”
Section: Introductionmentioning
confidence: 99%